Lithium-Ion Batteries - Thin Film for Energy Materials and Devices 2020
DOI: 10.5772/intechopen.81406
|View full text |Cite
|
Sign up to set email alerts
|

TiO2Nanoparticles Prepared by Sol-Gel Method for Anode Application in Lithium-Ion Batteries

Abstract: TiO 2 nanoparticles are prepared via sol-gel method using titanium tetraisopropoxide (TTIP) as a precursor under refluxing and controlled pH. It is found that pure anatase phase is obtained with pH 10. Further characterization studies are carried out on pure nanoparticle anatase phase by XRD, SEM, and transmission electron microscope (TEM). Their electrochemical performances as anode material in lithium-ion batteries are investigated by cyclic voltammetry, galvanostatic cycling, and rate capability measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…[17] Uniform thin layers can be fabricated by spray pyrolysis, the deposition method we are using, with the advantage of being low cost and rather simple to implement. [18] Several studies have shown the superiority of TiO 2 layers such as the TiO 2 is nontoxic and biocompatibility than cadmium oxide [19][20][21] and good sensing properties than ZnO. [22] The application of TiO 2 in sensor devices requires that TiO 2 has the following characteristics: good crystallization, semiconductor, porous films, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Uniform thin layers can be fabricated by spray pyrolysis, the deposition method we are using, with the advantage of being low cost and rather simple to implement. [18] Several studies have shown the superiority of TiO 2 layers such as the TiO 2 is nontoxic and biocompatibility than cadmium oxide [19][20][21] and good sensing properties than ZnO. [22] The application of TiO 2 in sensor devices requires that TiO 2 has the following characteristics: good crystallization, semiconductor, porous films, and so forth.…”
Section: Introductionmentioning
confidence: 99%